Shopping centers, espaço de lazer para idosos - Carneiro, Marnielly Barbosa (2022)
The emergence of new technologies and advances in science have promoted rapid population growth, with falls in birth, mortality and fertility rates and an increase in life expectancy. In Brazil, population aging gained more strength from the second half of the 20th century. Seeking to guarantee a better quality of life for the elderly, much has been said about the so-called active aging, in relation to which leisure is an essential permissible element of an unquestionable level of socialization that justifies the strengthening of Brazilian shopping malls in specialized leisure centers. Based on qualitative research, an analysis will be carried out to apprehend the resizing of shopping malls in the face of the problem of population aging, emphasizing the design of strategies, procedures and actions associated with the dimension of leisure for the elderly in some of these spaces in Fortaleza - CE. Roughly speaking, a kind of unfolding already envisioned in the domain of the city is presented, with an indication, on the part of the Public Power, of actions to resize the usufruct of public spaces by the elderly population. In Fortaleza, this scenario is no different, and it is possible to perceive the search for leisure in the private spaces of the city's shopping malls; sought after, mostly by women, on weekdays and in the afternoon. These shopping centers noticed the increase in the presence of this public and developed a series of actions and projects aimed at the social inclusion and leisure of the elderly. Thus, as a leisure center and space initially aimed at young and adult audiences, they adapt to the new scenario in which the elderly make up a potential consumer public. From the above, we will build an analysis comparing the phenomenon of population aging in Brazil, Ceará and Fortaleza; understand the presence of the elderly population of Fortaleza in shopping malls and, in turn, understand them as a place of leisure for the elderly, identifying the spaces, projects and actions implemented. This research was divided into 4 main stages: bibliographic research, field research through observation, elaboration and carrying out of interviews and analysis of the information obtained for the final writing of the dissertation.